The intersectoral links in the promotion of workers health - Michele Dias de Oliveira; Bruna Parnov Machado; Tanise Finamor Ferreira; Odete Teresinha Portela; Marlene Kreutz Rodrigues; Suzinara Beatriz Soares de Lima; Clara Leonida Marques Colomé (Universidade Federal de Santa Maria, 2012)
Objectives: to report experiences developed through intersectoral coordination for Promotion of Health of reforestation workers in the town of Unistalda, Rio Grande do Sul. Method: the methodology included theatrical, recreational activities, group dynamics, educational contest, individual conversations and lectures. The closing of the process used multidisciplinary approach to issues concerning the health problems most frequently raised among the group. Results: the action occurred trough the health care/educative actions about the interaction between health-work-disease from the profile of workers. The actions problematized determinants of the process health-jobseeking and behaviors favorable to a healthy lifestyle. Conclusions: the integration between the Family Health Unit, the Company of Reforestation and graduate course in Nursing of the Regional Integrated High Uruguay and Missions Campus Santiago, allowed the promotion of activities about health care and educational interventions directed to the integrality of health care to workers' health